The Application of the Polyvagal Theory to High Conflict Co‐Parenting Cases. (28th April 2020) - Bailey, Rebecca; Dana, Deborah; Bailey, Elizabeth; Davis, Frank
Abstract : Families, litigants, lawyers, advisors embroiled in cases of complex divorce with child contact issues, manage many stressors at once. Participants involved with these types of cases are often exhausted and burned‐out from the long‐term battles of prolonged litigation. The inability to problem‐solve or even communicate effectively reflects the chaos and traumatic stress of the experience and can be seen as a hallmark of this population. When people are consistently stressed, there is a breakdown of communication skills that can create an immunity to receiving help from any direction. Often all parties involved appear to be both hyper‐alert to potential threat, and hyper‐reactive to one another: no one feels safe. Stephen Porges' Polyvagal Theory is premised on the idea that neuroception plays a key role in the nervous system's ability to assess danger in the environment. Neuroception is a neurophysiological response that does not involve cognitive processing. When cognitive processing is not involved, the result may lead to misinterpretation of, and an inability to accurately assess situations: executive functioning including rational thinking and communication skills are lost to physiological response. Rather than evaluating families and individuals involved in the aforementioned complex divorce cases through the lens of pathology, Polyvagal Theory explains their behavior as an adaptive stress reaction. Utilizing Polyvagal Theory offers a promising path to treatment with these families and diminishing the poor communication and the heightened emotion, assisting practitioners in understanding the impact of neurobiological response in managing stress and trauma. Applying Polyvagal Theory to court involved populations can help both litigants and practitioners recognize the role of the autonomic nervous system, providing the opportunity to understand, to self‐regulate, and to improve communication and decision making. Key Points for the Family Court Community: Separation and divorce. The impact of Parent/Child contact problems in high‐conflict divorce and separation. The impact of high conflict co‐parenting cases on family law and mental health professionals. Interventions: Current practice Polyvagal theory. Polyvagal informed therapy. Effects of polyvagal approach and self regulation. Managing physiological response from a cognitive perspective. Clinical setting and polyvagal theory. Family therapy and polyvagal theory. Experiential framework and polyvagal theory. *Equine assisted therapy, polyvagal perspectives and alternatives. Processing chaos and grief. Other opportunities for making connection. Implementation for professionals.